2022
DOI: 10.1021/acs.analchem.1c04999
|View full text |Cite
|
Sign up to set email alerts
|

Blood Oxygen Sensor Using a Boron-Doped Diamond Electrode

Abstract: The electrochemical behavior of oxygen (O 2 ) in blood was studied using boron-doped diamond (BDD) electrodes. Cyclic voltammogram of O 2 in a 0.1 M phosphate buffer solution solution containing 1 × 10 −6 M of bovine hemoglobin exhibits a reduction peak at −1.4 V (vs Ag/ AgCl). Moreover, the scan rate dependence was investigated to study the reduction reaction mechanism, which was attributable to the reduction of O 2 to H 2 O 2 via two electrons. A linear calibration curve was observed in the concentration ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…increasing year by year and several review articles and books on diamond-based electrodes have now been published. [1][2][3][4][5][6][7][8][9][10] For the last 20 years, our research group have reported not only fundamental studies on BDD, but also on several novel electrochemical applications such as electrochemical sensors (including biomedical), [11][12][13][14][15][16][17][18] electrochemiluminescence, [19][20][21][22] and electrochemical organic synthesis. [23][24][25] These applications are due to the unique properties of BDD electrodes, and they could not be achieved using conventional electrodes.…”
mentioning
confidence: 99%
“…increasing year by year and several review articles and books on diamond-based electrodes have now been published. [1][2][3][4][5][6][7][8][9][10] For the last 20 years, our research group have reported not only fundamental studies on BDD, but also on several novel electrochemical applications such as electrochemical sensors (including biomedical), [11][12][13][14][15][16][17][18] electrochemiluminescence, [19][20][21][22] and electrochemical organic synthesis. [23][24][25] These applications are due to the unique properties of BDD electrodes, and they could not be achieved using conventional electrodes.…”
mentioning
confidence: 99%